LOCOMOTOR TRAINING WITH PARTIAL BODY WEIGHT SUPPORT: BRAZILIAN LITERATURE REVIEW. (Fiep Bulletin - online, 2016)
Introduction: Locomotor training with partial body weight support (PBWS) is a system consisting of a treadmill and a metal structure, in which the individual is mechanically supported by a safety harness above a treadmill, offering partial support of body weight of the individual, keeping it in the standing position while the lower limbs move, producing stimuli associated to gait. Objective: Revise the existing Brazilian literature on the use of locomotor training with PBWS for gait rehabilitation in various dysfunctions of deambulation. Method: a literature survey of scientific articles related to the PBWS in Scielo and Lilacs databases, using the keywords "partial body weight support," "robotic therapy" and associated words "training" and "gait" published in the last seven years was conducted. We considered only studies in Portuguese, in the original paper format, with full text available for free access, posteriorly there was the screening by title and abstract, which should correlate keywords. Results: Initially 130 articles were found, of which only seven met the inclusion criterion. The analysis showed that best results are obtained with gait training with PBWS than with conventional gait training, providing favorable physiological and psychological effects to patients, regardless of the training protocol used, besides showing improvement in gait phases. Conclusion: The gait training with PBWS is a safe and reliable means which appeared to innovate functional gait rehabilitation, thereby resulting in sustaining the body against gravity, providing relief from the burden of the lower extremities symmetrically, stabilizing the trunk, controlling the balance and reducing the risk of falling and injury.
Keywords: Locomotor training; partial body weight support; gait.